Berberine Alleviates 1-Methyl-3-Nitro-1-Nitrosoguanidine Induced Chronic Atrophic Gastritis in Rats - Wang, Lingling; Xie, Liqun (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Berberine (BBR), an isoquinoline alkaloid derived from Berberis plants, exhibits anti-inflammatory, anti-cancer, and antioxidant properties. This study explored the role of BBR in chronic atrophic gastritis (CAG). Materials and Methods: The 1-methyl-3-nitro-1-nitrosoguanidine and an irregular diet were used to establish the CAG model. Chronicatrophic gastritis rats were administered BBR at different doses via gavage, and teprenone (TEP) served as the positive control drug. We monitored and measured changes in body weight and food intake, pepsin activity, and gastric acid levels in the rats. Hematoxylin and eosin staining was utilized to scan the pathological condition in the gastric mucosal tissue of rats, while enzyme-linked immunosorbent assay was utilized to analyze alterations in serum inflammatory factors and hormone levels. Western blot was employed to evaluate protein expression. Additionally, 16S rRNA was conducted to assess changes in the intestinal flora of CAG rats. Results: Berberine increased body weight and food intake, improved gastric atrophy, and enhanced pepsin activity and total acidity of gastric juice in CAG rats. BBR treatment led to decreased levels of inflammation factors and motilin, while gastrin and somatostatin levels were elevated in CAG rats. Additionally, BBR inhibited the NF-κB and MAPK pathway in these rats. Berberine treatment also regulated the composition and abundance of intestinal flora. These microbiome alterations suggest a possible role in modulating gut inflammation associated with CAG. Conclusion: Berberine may alleviate CAG injury by reducing inflammation and regulating intestinal flora, which may be closely associ ated with the NF-κB and MAPK pathways. Cite this article as: Wang L, Xie L. Berberine alleviates 1-methyl-3-nitro-1 nitrosoguanidine-induced chronic atrophic gastritis in rats. Turk J Gastroenterol. 2025;36(11):723-731.